Transregnal kingship in the thirteenth century - Peltzer, Jörg; Vincent, Nicholas (Proceedings of the British Academy, 2025)
Transregnal Kingship in the Thirteenth Century explores a wide-spread European phenomenon: rulership over multiple kingdoms, or a kingdom in combination with major non-royal lordships elsewhere. Perceptions of royal authority and kingly sovereignty changed significantly during the thirteenth century, and as the role played by kingdoms as sovereign polities was strengthened, the framework for transregnal kingship shifted. This volumes investigates the consequences, examining the theory, perception and administrative practices of transregnal kingship. Intended to provide a coherent picture that itself may facilitate comparisons, the work focuses on four distinct, but significantly intertwined polities: The Empire, France, The Angevin Empire, and the Papacy. Despite its frequent occurrence, transregnal kingship played a relatively small role in contemporary political thought, and transregnal practice took a great variety of forms, showing rulers and the ruled adapting to circumstance rather than pursuing any pre-conceived grand strategy. Meanwhile, the ruler’s frequent physical absence provoked the creation of multiple forms of vice-regal power. In the Empire, it also led to an increased use of arbitration as a means to solve disputes at regional level. Finally, an analysis of architecture and the built environment suggests that such things exhibit a fascinating combination of the political and the merely fashionable